The Effect of Work Motivation, Work Discipline and Compensation on Employee Performance in the Customer Care Unit of Bandung Adventist Hospital - Anita Sukmawati; Rudianto Rudianto; Dwi Hernuningsih; Freddy Johannis Rumambi; Marisi Pakpahan (International Forum of Researchers and Lecturers, 2024)
Employee performance, particularly in the customer care department, is crucial as all aspects of hospital care related to patient experience. Effective and responsive interactions can enhance patient satisfaction, build trust, and create a supportive environment that aids the healing process. Additionally, customer care employees serve as a bridge between patients and medical staff, ensuring that patients' needs and inquiries are addressed with distinction. Therefore, it is essential for hospital management to maintain employee performance by providing work motivation, discipline, and appropriate compensation. This study aims to analyze the partial and simultaneous effects of work motivation, work discipline, and compensation on improving employee performance in the Customer Care Department of Bandung Adventist Hospital. This descriptive quantitative research was conducted with 30 customer care employees at Bandung Adventist Hospital in early September 2024. The findings indicate that work motivation and compensation do not significantly affect employee performance according to the data analysis, whereas work discipline has a significant impact on employee performance. However, when considered together, work motivation, work discipline, and compensation collectively have a significant effect, accounting for 44.1% of the variance. From this data, it can be concluded that maintaining work motivation, discipline, and compensation together can help sustain employee performance in the Customer Care Department of Bandung Adventist Hospital.